« Faire la ferraille » en banlieue parisienne : glaner, bricoler et transgresser - Bénédicte Florin; Pascal Garret (EchoGéo)
Scrap collectors are men or women who collect abandoned metals in the streets, which are sorted, tinkered, resold to wholesalers and, finaly, reintegrated into the metallurgy industry. Gleaning scrap is a do-it-yourself job, most often done by people in situations of economic and social precariousness. These contemporary gatherers realize their activities in urban margins, as many resource areas. The interviews conducted in the Paris suburbs show that, by their practices and know-how, they overcome the obstacles that their personal situation and their activity, more or less tolerated, impose. They also reveal a hierarchy within the scrap collectors and the specific place assigned to the Roma figure.